KARAKTERISTIK DAN LUARAN PREEKLAMPSI DI RSUP PROF. DR. R.D. KANDOU MANADO - Silomba, Wahyuni; Wantania, John; Kaeng, Joice (Universitas Sam Ratulangi, 2013)
Abstract: Maternal mortality is still one of the world health problems. It was estimated that more than 536,000 women per year died due to labor. In 2007, Indonesia maternal mortality rate (MMR) was 248 per 100,000 live births, which was the highest among SoutheastAsia countries. The most frequent cause of maternal mortality is hypertension in pregnancy. The insidence of pre-eclampsia in Indonesia is approximately 3-10% of all cases of pregnancies, which is 23.6 per 1,000 births. This study aimed to determine the characteristics and outcomes of pre-eclampsia in Prof. Dr. R.D Kandou General Hospital Manado. This was a retrospective descriptive study. Data were obtained from the medical records of pre-eclampsia patients from January 1 until December 31, 2011 at the Department of Obstetrics Gynecology Clinic. There were 328 patients admitted to the hospital with a diagnosis of pre-eclampsia or eclampsia. The data consisted of 121patients with mild pre-eclampsia, 103 patients with severe pre-eclampsia, 86 patient with superimposed pre-eclampsia, and 18 patients with eclampsia. Maternal deaths were 11.1 %. Perinatal deaths in mild preeclampsia were 1.6%; in severe preeclampsia 3.8%; in super-imposed pre-eclampsia 3.5%; and in eclampsia 11.1%. Conclusion: The most frequent cases of pre-eclampsia were mild pre-ecxlampsia, followed by severe pre-eclampsia, super-imposed pre-eclampsia, and eclampsia respectively. Perinatal deaths were the highest in eclampsia cases. Keywords: preeclampsia, superimposed, eclampsia, maternal death, perinatal death. Abstrak: Kematian ibu masih merupakan salah satu masalah kesehatan dunia. Diperkirakan lebih dari 536.000 ibu per tahunnya meninggal akibat persalinan.Di Indonesia Angka Kematian Ibu (AKI) tahun 2007 adalah 248 per 100.000 kelahiran hidup, yang tertinggi dibandingkan negara-negara di Asia Tenggara. Salah satu penyebab kematian ibu bersalin paling sering yaitu hipertensi dalam kehamilan. Angka kejadian preeklampsi di Indonesia sekitar 3 – 10% dari semua jumlah kehamilan yaitu 23,6 kasus per 1.000 kelahiran. Penelitian ini berttujuan untuk mengetahui karakteristik dan luaran preeklampsi (PE) di BLU RSUP Prof. Dr. R. D Kandou Manado.Penelitian ini bersifat retrospektif deskriptif dengan melihat data rekam medik pasien PE periode 1 Januari – 31 Desember 2011 di Bagian Obstetri-Ginekologi. Terdapat 328 pasien yang dirawat dengan diagnosis PE sampai eklampsi, terdiri dari 121 preeklampsi ringan (PER), 103 preeklampsi berat (PEB), 86 superimposed preeklampsi, dan 18 eklampsi. Kematian maternal sebesar 11,1%. Kematian perinatal pada PER sebanyak 1,6%, PEB sebesar 3,8%, super-imposed PE sebesar 3,5%; sedangkan eklampsi sebesar 11,1%. Simpulan: Jenis preeklamsi yang tersering ialah PER, diikuti PEB, super-imposed preeklamsi, dan eklamsi. Kematian perinatal tertinggi pada kasus eklamsi. Kata kunci : preeklampsi, superimposed, eklampsi, kematian maternal, kematian perinatal.